Nanomaterials: A powerful tool for tumor immunotherapy - Chen, Ziyin; Yue, Ziqi; Wang, Ronghua; Yang, Kaiqi; Li, Shenglong (Frontiers in Immunology, 2022)
Cancer represents the leading global driver of death and is recognized as a critical obstacle to increasing life expectancy. In recent years, with the development of precision medicine, significant progress has been made in cancer treatment. Among them, various therapies developed with the help of the immune system have succeeded in clinical treatment, recognizing and killing cancer cells by stimulating or enhancing the body’s intrinsic immune system. However, low response rates and serious adverse effects, among others, have limited the use of immunotherapy. It also poses problems such as drug resistance and hyper-progression. Fortunately, thanks to the rapid development of nanotechnology, engineered multifunctional nanomaterials and biomaterials have brought breakthroughs in cancer immunotherapy. Unlike conventional cancer immunotherapy, nanomaterials can be rationally designed to trigger specific tumor-killing effects. Simultaneously, improved infiltration of immune cells into metastatic lesions enhances the efficiency of antigen submission and induces a sustained immune reaction. Such a strategy directly reverses the immunological condition of the primary tumor, arrests metastasis and inhibits tumor recurrence through postoperative immunotherapy. This paper discusses several types of nanoscale biomaterials for cancer immunotherapy, and they activate the immune system through material-specific advantages to provide novel therapeutic strategies. In summary, this article will review the latest advances in tumor immunotherapy based on self-assembled, mesoporous, cell membrane modified, metallic, and hydrogel nanomaterials to explore diverse tumor therapies.